2010
DOI: 10.1074/jbc.m109.068395
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Sphingosine Kinase 1 to the Plasma Membrane Is Mediated by Calcium- and Integrin-binding Protein 1

Abstract: SK1 (sphingosine kinase 1) plays an important role in many aspects of cellular regulation. Most notably, elevated cellular SK1 activity leads to increased cell proliferation, protection from apoptosis, and induction of neoplastic transformation. We have previously shown that translocation of SK1 from the cytoplasm to the plasma membrane is integral for oncogenesis mediated by this enzyme. The molecular mechanism mediating this translocation of SK1 has remained undefined. Here, we demonstrate a direct role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(168 citation statements)
references
References 39 publications
8
159
0
1
Order By: Relevance
“…Interestingly, this CIB1 interaction site F197/L198 [24] overlaps with the hydrophobic patch that has been shown to be important for direct membrane binding in a previous study [23] and this work. As suggested by Jarman et al [24], it is possible that CIB1 acts as a "molecular shepherd" to bring SK1 close enough to the membrane but does not influence SK1s intrinsic mechanism for binding to membranes. However, it is also likely that CIB1 can "override" the intrinsic mechanism of SK1 membrane binding and force it to the membrane as a function of the myristoyl-switch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this CIB1 interaction site F197/L198 [24] overlaps with the hydrophobic patch that has been shown to be important for direct membrane binding in a previous study [23] and this work. As suggested by Jarman et al [24], it is possible that CIB1 acts as a "molecular shepherd" to bring SK1 close enough to the membrane but does not influence SK1s intrinsic mechanism for binding to membranes. However, it is also likely that CIB1 can "override" the intrinsic mechanism of SK1 membrane binding and force it to the membrane as a function of the myristoyl-switch.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane localization of SK1 has also been attributed to interaction with CIB1 [24,25], which acts as a calcium-myristoyl switch. Interestingly, this CIB1 interaction site F197/L198 [24] overlaps with the hydrophobic patch that has been shown to be important for direct membrane binding in a previous study [23] and this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this, we interfered with the ability of SPHK-1 to translocate to synapses by mutating its calcium/calmodulin (CaM)-binding site. Mutations in the CaM-binding site of mammalian SphK have been reported to decrease translocation of SphK to membranes but to have no effect on its catalytic activity (Sutherland et al 2006;Jarman et al 2010). We found that GFP-tagged SPHK-1 transgenes lacking the functional CaM-binding site [SPHK-1(DCaM) -GFP] were expressed at levels in the cell bodies of neurons similar to wild-type transgenes [cell body fluorescence was 2280 6 243 arbitrary units for SPHK-1(WT)-GFP and 2561 6 222 arbitrary units for SPHK-1(DCaM)-GFP; n = 20].…”
Section: Sphk-1 Functions At Presynaptic Terminalsmentioning
confidence: 99%
“…SK (which exists as two isoforms termed SK1 and SK2) is activated by agonists such as antigen, plateletderived growth factor, nerve growth factor, tumor necrosis factor ␣, and epidermal growth factor (EGF), resulting in an increase in intracellular S1P. SK1 activation and/or translocation is regulated by phosphorylation catalyzed by ERK-1/2 and by CIB1 (calcium and integrin-binding protein 1) (14,15). S1P has an important role in breast cancer cells in terms of regulating survival, proliferation, and migration (16 -18).…”
mentioning
confidence: 99%